THE FUNCTION OF BATAJA DANCE IN SEMANDANG KIRI VILLAGE, SIMANG HULU DISTRICT, KETAPANG REGENCY, WEST KALIMANTAN - Puspita Heniwati Yuliani; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The purpose of the Bataja Dance in the Simpakng Dayak tribe's wedding ritual in Simpang Hulu District, Ketapang Regency, West Kalimantan, piqued researchers' intense interest and served as the driving force for this study. In Semandang Kiri Village, Simpang Hulu District, Ketapang Regency, a wedding ritual is performed. This study's main goal is to describe this ritual's execution. What role does the Bataja dance have in the Simpakng Dayak community's wedding ceremonies? The research strategy is anthropological, and the method utilized is a descriptive method in the form of qualitative research. The information in this study pertains to the Simpakng Dayak tribe's ritual practices that take place during wedding ceremonies. With Mr. Rapael Kalong, Mr. Kornelius Kolik, and Mr. Laurensius Kayan serving as resource individuals with in-depth knowledge of the Bataja dance, thedata were evaluated qualitatively. Results from observations, interviews, and documentation serve as the basis for the data. During the research, an anthropological review with analytical methodologies was used to assess the validity of the data using the observation extension methodology, and it was also used to analyze the data. Following is a conclusion that may be drawn from the data analysis. The Bataja dance serves two purposes: it is both a ritual and a kind of entertainment. The purpose of the bataja dance as a ceremony is to convey the thanks of the locals to Duata/God for the bride and groom who have been recognized by the Dayak Simpakng custom. As a form of entertainment, the bataja dance serves the purpose of being accessible to anyone who wishes to take part in the dance itself